Differences in neurology residency training programmes across Europe – a survey among the Residents and Research Fellow Section of the European Academy of Neurology national representatives. (1st May 2020) - Kleineberg, N. N.; van der Meulen, M.; Franke, C.; Klingelhoefer, L.; Sauerbier, A.; Di Liberto, G.; Carvalho, V.; Berendse, H. W.; Deuschl, G.
Abstract : Background and purpose: Neurology is rapidly evolving as a result of continuous diagnostic and therapeutic progress, which influences the daily work of neurologists. Therefore, updating residency training programmes is crucial for the future of neurology. Several countries are currently discussing and/or modifying the structure of their neurology residency training programme. A detailed and up‐to‐date overview of the available European residency training programmes will aid this process. Methods: A questionnaire addressing numerous aspects of residency training programmes in neurology was distributed among 38 national representatives of the Resident and Research Fellow Section of the European Academy of Neurology. Results: We obtained data from 32 European countries (response rate 84%). The median (range) duration of the residency training programmes was 60 (12–72) months. In the majority of countries, rotations to other medical disciplines were mandatory, mostly psychiatry (69%), internal medicine (66%) and neurosurgery (59%). However, the choice of medical fields and the duration of rotations varied substantially between countries. In 50% of countries, there were formal regulations regarding training in evidence‐based medicine, teaching skills and/or leadership qualities. In many countries (75%), residents had to take an examination. Conclusions: We found substantial variation among European countries in the duration of residency training programmes, and especially in the choice of obligatory rotations to external medical disciplines. Despite a presumably similar spectrum of patients, neurology residency training programmes across Europe are not harmonized. The structure of the programme should be determined by its relevance for neurologists today and in the future.